2005
DOI: 10.1016/j.febslet.2005.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity and adhesion of resting and lipopolysaccharide‐stimulated macrophages

Abstract: Colloidal Force Microscopy was employed to study the viscoelastic and adhesive properties of macrophages upon stimulation with lipopolysaccharide (LPS). Force vs. distance measurements were performed. The adhesion of LPS-stimulated cells (separation force = 37 ± 3 nN) was almost twice as high as that of resting macrophages (16 ± 1 nN). Upon retraction pulling of membrane tethers was observed. Tether lengths and forces at which rupture take place did not depend on stimulation. The reduced Young's modulus K, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 27 publications
6
54
0
Order By: Relevance
“…Since the cell is heterogeneous, mechanical properties will vary widely between local areas and the whole cell. Young's modulus previously measured with a spherical probe is 0.2-1.2 kPa for breast cancer cells [21,27], and is 0.5 kPa for macrophages [28]. Thus the 0.1-1.4 kPa values presented here for Young's modulus of RBCs, Raji, Hut, and K562 cells are comparable to those published previously.…”
Section: Resultssupporting
confidence: 78%
“…Since the cell is heterogeneous, mechanical properties will vary widely between local areas and the whole cell. Young's modulus previously measured with a spherical probe is 0.2-1.2 kPa for breast cancer cells [21,27], and is 0.5 kPa for macrophages [28]. Thus the 0.1-1.4 kPa values presented here for Young's modulus of RBCs, Raji, Hut, and K562 cells are comparable to those published previously.…”
Section: Resultssupporting
confidence: 78%
“…57 For macrophages, research has showed that the Young's modulus of macrophages was in the range of 0.5−2 kPa. 58 Recent research showed that the cell mechanical properties determined the macrophage functions. 59 Here the measured Young's modulus of macrophages was in the range of 1−3 kPa and became 2−5 kPa after the activation of phagocytosis, comparable to the measured values of the cell Young's modulus by other groups.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, researchers have used sphere tips to quantify the mechanical properties of the whole living cells [16,35,38,39]. Compared with conical tips, sphere tips have larger contact areas and thus smaller applied pressures, causing that cellular Young's modulus measured with sphere tips is less than that with conical tips [40]. Despite this difference, the studies by Rico et al [41] have showed that the change trend of cellular Young's modulus measured using sphere tips was consistent with that using conical tips.…”
Section: Discussionmentioning
confidence: 99%